Improvements in investment efficiency prior to a mandated accounting change: Evidence from ASC 842 - Christensen, Derek; Lynch, Daniel P.; Partridge, Clay (Contemporary Accounting Research, 2025)
Abstract Prior literature on the relationship between financial reporting and investment efficiency generally overlooks the connection between firms' financial and managerial reporting systems. As a result, it is difficult to determine whether increases in the quality of firms' internal information environments (IIQ) and/or the quality of their external information environments (EIQ) explain improvements in investment efficiency following financial reporting changes. Leveraging the transition window to the new lease standard (Accounting Standards Codification [ASC] 842), we use a difference‐in‐differences design and find that firms that materially change their internal controls due to ASC 842 (treatment firms) significantly improve their investment efficiency in the final year of the transition window. Multiple falsification tests rule out that contemporaneous improvements in treatment firms' EIQ explain our finding. Additional channel analyses suggest the increases in IIQ for treatment firms predominantly alleviate moral hazard risk between central and divisional managers within the firm, leading to a reduction in empire building. Our findings extend the literature on the relationship between financial reporting and investment efficiency. They also contribute to the literature on the consequences of ASC 842 by answering the FASB's call for research on how ASC 842 affects firms' asset utilizations.